2014
DOI: 10.1111/papt.12037
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of compassion focused therapy following acquired brain injury

Abstract: CFT appears to be a feasible intervention for psychological problems after ABI. CFT was associated with a reduction in symptoms of anxiety and depression and associated self-criticism, as well as enhanced self-reassurance for ABI survivors. These ABI survivors reported that CFT provided them with tools to manage continued psychological difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 45 publications
(54 reference statements)
2
48
0
4
Order By: Relevance
“…Six participants engaged in basic compassion practices, including soothing rhythm breathing, and flows of compassion. Most were also able to discuss concepts related to compassion, such as “threat” and “self‐soothing.” These findings are consistent with Poz's and Collins, Gilligan and Poz's initial reports of using CFT in PWD, and the success of adapting CFT for populations with cognitive impairments …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Six participants engaged in basic compassion practices, including soothing rhythm breathing, and flows of compassion. Most were also able to discuss concepts related to compassion, such as “threat” and “self‐soothing.” These findings are consistent with Poz's and Collins, Gilligan and Poz's initial reports of using CFT in PWD, and the success of adapting CFT for populations with cognitive impairments …”
Section: Discussionsupporting
confidence: 88%
“…Collins, Gilligan and Poz's 15 initial reports of using CFT in PWD, and the success of adapting CFT for populations with cognitive impairments. 10,11 4.1 | Implications for practice and research CFT might improve mood and anxiety and may be particularly relevant in this client group, as a diagnosis of dementia and its associated neurological impairments can leave individuals vulnerable to feelings of shame, 12 and experiencing a sense of "existential threat." 14 The flexibility of the manual allowed for adapting CFT to the person's cognitive ability and "openness" to compassion; however, the study found it could not be sufficiently covered in 10 sessions.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for bias is known to be inherent to case studies, case series and quasi-experimental studies due to sampling, selection and measurement biases. Applying the assigned quality descriptors for single-participant studies, three case studies were rated as Low quality (Ashworth, 2014;Ashworth et al, 2011;Gillanders et al, 2015) and two case studies were rated as Moderate quality (Gillanders & Gillanders, 2014;Shields & Ownsworth, 2013). All included studies specified measures of target behaviours and reported raw data points, with the majority using statistical analysis.…”
Section: Quality Assessment For Non-randomised Designsmentioning
confidence: 99%
“…The range of definitions and measures used in the studies in this special section reflects not only the breadth of concepts relevant to positive outcomes, but also the fact that applying positive perspectives to the study of ABI is a relatively new endeavor. Nonetheless, rehabilitation researchers are already exploring the efficacy of positive psychology, positive parenting interventions, and health and wellness programs for promoting optimal outcome in individuals with ABI (e.g., Andrewes et al, 2014;Antonini et al, 2012;Ashworth et al, 2015;Brenner et al, 2012). The conceptual boundaries between the constructs of positive psychology, plasticity, reserve, resilience, character strengths, coping, healthy behaviors, optimal outcome, quality of life, and wellness may well be somewhat blurry.…”
Section: Introductionmentioning
confidence: 99%